Analisis Tingkat Kesehatan Bank Menggunakan Metode Risk Profile, Good Corporate Governance, Earning dan Capital Pada PT. Bank Cimb Niaga Tbk - Marti Dewi Ungkari (Jurnal Wacana Ekonomi, 2018)
Banks must always be assessed for their soundness level in order to continue to provide excellent service to customers, because an unhealthy bank condition will endanger various parties, not only endanger the bank itself. One of the methods used to assess the soundness of a bank can use the currently applicable method, namely the Risk Profile, Good Corporate Governance, Earning and Capital (RGEC) method. The purpose of this research is to determine the Rating of Bank Soundness at PT. Bank CIMB Niaga Tbk in terms of RGEC. This research is in the form of descriptive quantitative research, in which the procedures for health assessment refer to the Circular and regulations that have been established by Bank Indonesia in 2011, namely SE No. 13/24 / DPNP and PBI No. 13/1 / PBI / 2011. The Risk Profile factor is measured using the NPL and LDR ratios, obtaining the predicate Fairly Healthy, the Good Corporate Governance factor by analyzing the results of the GCG self-assessment of the Bank obtains the predicate Healthy, Earning is measured using the ratio ROA, ROE, NIM and BOPO obtains the predicate Fairly Healthy and Capital is measured using the ratio CAR received the predicate Very Healthy.